Effects of coffee tree seedling inoculation with increasing amounts of spores of the endomycorrhizal fungus Gigaspora margarita - Siqueira, José Oswaldo; Filho, Arnaldo Colozzi; Junior, Orivaldo José Saggin (Pesquisa Agropecuaria Brasileira, 1994)
The effects of inoculation with increasing amount spores of the endomycorrhizal fungus Gigaspora margarita on mycorrhizal root colonization, growth and nutrition of coffee tree seedlings were studied in a greenhouse experiment. At transplanting, seedlings were inoculated with spore suspensions adjusted to deliver 0, 50, 100, 200 and 800 spores/plant and with an additional treatment of soil inoculum (200 spores/plant). Plant dry weight after 140 days of growth was improved by as much as 7.4 fold by inoculation as compared to control. After 30 days of transplant, root colonization rates increased linearly with increasing spore number per plant, and did not show such increase in later periods. Increasing spore numbers accelerated colonization; however, additional growth benefits were not found when more than 100 spores were delivered per plant. Soil inoculum showed to be more effective than the equivalent spore suspension. Seedling growth increase was related to improved plant uptake of phosphorus and potassium.